Detection of The Quaternary Ammonium Compound Antiseptic Resistance Gene (qac A/B qac C and qac E gene) In Pseudomonas Aeruginosa Recovered from Topical Wound Infection - Ahmed, Sara S; Hassan, Jabbar S.; Mahdi, Qahtan A. (International Journal of Membrane Science and Technology, 2023)
Background: Quaternary ammonium compounds (QACs) have represented one of the most visible and effective classes of antiseptics and disinfectants substances that used in different parts of life including food production, water treatment and healthcare such as hospitals to prevent infections and intoxications. The increased use of disinfectants containing quaternary ammonium compounds (QACs) has raised concerns about the development of resistance. Aim of the study: this study pursues to determination frequency of antiseptic resistant Quaternary Ammonium Compound (qacA/B, qacC and qacE gene) in Pseudomonas aeruginosa, recovered from topical wound infection. Methods: Two swab samples were collected from 200 patients complain from burn, traumatic injury and wound after surgery, Suspected isolates of P. aeruginosa which showed Beta hemolysis on Blood agar media while occur colorless colonies (non-lactose fermenter) on MacConkey. Furthermore, identified using VITEK-2 System. The efficacy of antiseptics chlorhexidine (CLX), benzalkonium (BZK) and cetrimide (CET) was tested against P. aeruginosa by Well diffusion assay test and MIC procedure. The confirmed P. aeruginosa isolates have been used for Genomic DNA extraction from a fresh overnight culture, after that DNA templates was used to target (qacA/B, qacC and qacE gene) by using specific Primers sequences. Results: Out of 56 P. aeruginosa a considerable number of isolates 48 (85.7%) of them were resistance to chlorhexidine and 8 (14.3%) were sensitive, moreover substantial number of isolates 42 (75.0%) of them were resistance to cetrimide and 14 (25.0%) were sensitive; No sensitive rate to benzalkonium were observed in all isolates, qacA/B gene were identified in 32(57.1%) were positive for this gene while qacC gene were detected in 46(82.1%) were positive for this gene, Furthermore, qacE gene were detected in 50 (89.2%) were positive for this gene in 56 P. aeruginosa isolates. Conclusion: the current study, shows that the qacA/B, qacC and qacE genes which harbored resistance to quaternary ammonium compound antiseptics are widespread in Pseudomonas aeruginosa isolates in wound and burn patients.